Gender Influence on Career Preferences in STEM: Unraveling Stereotypes and Fostering Diversity (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2022)
This research investigates the influential role of gender in shaping career preferences within the fields of science and technology (STEM). The study explores the extent to which gender-related factors impact career aspirations and the potential implications for gender diversity in STEM industries. Through a mixed-methods approach, combining qualitative interviews and quantitative surveys, data were collected from a diverse sample of individuals across various age groups and educational backgrounds. The research sought to identify patterns and trends in career preferences, particularly in relation to STEM disciplines. The findings of this study reveal significant disparities in career preferences between males and females. Gender stereotypes, societal expectations, and early educational experiences were identified as key determinants in driving these disparities. Women often reported feeling constrained by stereotypes associated with certain STEM fields, while men tended to gravitate toward traditionally "masculine" STEM careers. Education emerged as a crucial factor in influencing career choices. Exposure to inclusive and diverse STEM education environments was found to challenge gender-based biases and encourage individuals to explore a broader range of STEM opportunities. The implications of these findings extend beyond academia. Achieving gender equality in STEM is recognized as both a societal imperative and a catalyst for innovation. The research emphasizes the importance of implementing strategies such as mentorship, social support, and inclusive educational practices to bridge the gender gap in STEM. In conclusion, this research underscores the need for continued efforts to understand and address the complex interplay between gender and career choices in STEM. By fostering inclusivity and dismantling gender stereotypes, we can create a future where STEM fields are enriched by a diverse array of talents, enabling greater progress and innovation in science and technology